1999
DOI: 10.1172/jci6861
|View full text |Cite
|
Sign up to set email alerts
|

Association of mannose-binding lectin gene heterogeneity with severity of lung disease and survival in cystic fibrosis

Abstract: Mannose-binding lectin (MBL) is a key factor in innate immunity, and lung infections are the leading cause of morbidity and mortality in cystic fibrosis (CF). Accordingly, we investigated whether MBL variant alleles, which are associated with recurrent infections, might be risk factors for CF patients. In 149 CF patients, different MBL genotypes were compared with respect to lung function, microbiology, and survival to end-stage CF (death or lung transplantation). The lung function was significantly reduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
299
5
14

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 399 publications
(344 citation statements)
references
References 43 publications
26
299
5
14
Order By: Relevance
“…Structural variants have been associated with a wide range of infectious and autoimmune disorders. [38][39][40] In our study, there was no association observed between the structural variants of MBL2 and susceptibility to filarial infection. However, we found a possible association between the promoter polymorphism at bp −221 (designated X and Y) and resistance to infection; filarial infection is less common in individuals with the XX genotype, associated with decreased circulating levels of MBL, independent of the structural allele genotype.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Structural variants have been associated with a wide range of infectious and autoimmune disorders. [38][39][40] In our study, there was no association observed between the structural variants of MBL2 and susceptibility to filarial infection. However, we found a possible association between the promoter polymorphism at bp −221 (designated X and Y) and resistance to infection; filarial infection is less common in individuals with the XX genotype, associated with decreased circulating levels of MBL, independent of the structural allele genotype.…”
Section: Discussioncontrasting
confidence: 79%
“…The classification of haplotypes as sufficient and insufficient is well described and separates into two groups, based upon circulating levels and functional differences in vitro, secondary to a structural variant (B, C or D). 39 Comparative analysis was performed at each of three loci using a 2 analysis (3 × 2 tables with 2 degrees of freedom) or a Fisher's exact test (f). MF+ indicates asymptomatic microfilaremia and CP indicates chronic lymphatic obstruction/ elephantiasis or hydrocele, collectively also known as chronic pathology.…”
Section: Genes and Immunitymentioning
confidence: 99%
“…4 MBL deficiency is associated with infection in infants with immature immunity, 8,9 and patients with autoimmune disorders 10 and cystic fibrosis. 11,12 An association of MBL deficiency and infection is also reported in patients treated with conventional chemotherapy 13,14 or high-dose myeloablative chemotherapy followed by allogeneic stem cell transplantation, 15 which is not confirmed by others. 16,17 In the present study, we report an increased risk of major bacterial infection in patients carrying the MBL polymorphism when treated with high-dose chemotherapy (HDT) followed by autologous peripheral blood stem cell transplantation (auto-PBSCT).…”
mentioning
confidence: 95%
“…[35][36][37] Structural exon 1 variants in MBL2 appear to modify pulmonary outcome in cystic fibrosis (CF) and rheumatological outcomes in chronic granulomatous disease. [38][39][40] We hypothesized that if there has been recent selection on MBL2 common genetic variation could result in selectively advantageous innate immune responses, depending upon the challenge. Moreover, the extent of linkage disequilibrium (LD) and haplotype diversity across MBL2 could provide signatures for selective pressure, however complex, and provide insight into whether the common alleles, B, C and D, have been maintained under balanced selection.…”
Section: Introductionmentioning
confidence: 99%